Hydrolysis of pork sarcoplasmic protein extracts by unique staphylococci isolated from low-salt dry-cured ham. (15th July 2022) - Ju, Ming; Piao, Chunxiang; Zhang, Jian; Mu, Baide; Li, Guanhao; Zhang, Wangang
Abstract: Dry-cured hams were produced using two curing agents with low-salt group and full-salt group. The salt content and the free amino acid (FAA) content were measured during the production process. The low-salt group was found to have a lower salt content ( P < 0.05) and a higher FAA content ( P < 0.05) in the final product than the other group. Three protease-producing strains ( Staphylococcus cohni, Staphylococcus saprophyticus and Staphylococcus equorum ) were further isolated from the low-salt hams, and their ability to hydrolyze proteins were assessed in porcine sarcoplasmic protein extracts. Gel electrophoresis showed that all strains were similar in their ability to degrade sarcoplasmic proteins. Samples inoculated with Staphylococcus saprophyticus had higher FAA content than those inoculated with the other two strains ( P < 0.05). Glycine and alanine were the most increased FAAs compared to the control group. The results suggest that the novel Staphylococcus saprophyticus isolated from dry-cured ham has potential as a starter for fermented meat products. Highlights: The low-salt ham had higher free amino acid contents than full-salt ham. Three protease-producing strains were isolated from low-salt ham. Staphylococci could well degrade sarcoplasmic protein and promote the generation of free amino acids. Staphylococcus saprophyticus was identified as an effective meat starter.